Leveraging video presentations to improve students’ presentation skills using TED Talks video - Syukrillah, Jazah; Farida, Alief Noor (ELT Forum: Journal of English Language Teaching, 2025)
This study explores the use of TED Talks as a tool for enhancing students' presentation skills. By analyzing TED speakers' use of key techniques such as structure, visuals, vocal delivery, and credibility, this research examines how these elements contribute to effective communication and audience engagement. The study identifies the core presentation skills emphasized by TED speakers and investigates how students can apply these strategies to improve their own presentations. The research also explores the role of structure and visuals in engaging and informing an audience, as well as the impact of vocal delivery on presentation effectiveness. Additionally, the study looks at how TED speakers establish credibility and how students can incorporate these techniques to enhance their presentations. The issue addressed in this study is the challenge of improving students' presentation skills in educational settings, where traditional teaching methods often fall short in preparing students for effective public speaking. The suggestions include integrating TED Talks into curricula to provide students with practical examples of high-quality presentations and to help them adopt best practices in their own presentations. The findings provide valuable pedagogical insights into how TED Talks can be integrated into educational settings to improve presentation skills and foster more engaging, confident public speaking among students.